72.4k views
1 vote
Simplify (√3 + √5) (√3 − √5)

User Kyungjin
by
4.6k points

2 Answers

5 votes

Answer:

-2

Explanation:

In order to expand this, we need to use FOIL (first, outer, inner, last).

The first term for each expression is √3, so we multiply those together first:

(√3) * (√3) = 3

The outer term for the first expression is √3 and the outer term for the second equation is -√5, so multiply these next:

(√3) * (-√5) = -√15

The inner term for the first expression is √5 and the inner term for the second equation is √3, so multiply these:

(√5) * (√3) = √15

The last term for the first expression is √5 and the last term for the second equation is -√5, so finally, multiply these:

(√5) * (-√5) = -5

Now, add all these together:

3 + (-√15) + √15 + (-5) = 3 - 5 = -2

The answer is -2.

Hope this helps!

User Mjlee
by
5.2k points
5 votes

Answer:

Explanation:

WE can see it is in the from of


a^(2) -b^(2)=
(a +b)(a-b)

So Now

=
(√(3) )^(2) - (√(5) )^(2)

= 3 - 5

= - 2

Hope it helps;)

User Toretto
by
4.5k points